ANALISIS KINERJA SOLAR CELL DENGAN SUMBER ENERGI SOLAR SIMULATOR - SETYO PAMUNGKAS, FENDI; ANSORI, ARIS (Jurnal Teknik Mesin, 2020)
The energy crisis has been a huge problem that becomes the world problem especially Indonesia. A new alternate energy is the most needed solution that can solve it, particulary colecticity energy. An energy utilization is extremely important for the sustainability of human life. One of the energy utilization is solar energy by using solar cell. The purpose of this research is for to know solar cell performance and solar cell efficiency that use a control system with the radiasion of the lights. This research is using experimental methot that the solar cell is controlled by the solar cell system that follow the movement of the lights radioation. The solar cell will be equipped with a simulator so that can read the latensity of the light. The data analysis in this research is descriptive that describe the result in from of table any grafick. From this research, the researcher want to get the ligh value of solar cell performance and solar cell efficiency. Based on this research at 12.30 am, the eficiency value of 40° inclination angle of solar cell with 110° inclination of solar simulator has 5,31% eficiency value of 50° inclination angle of solar cell with 110° inclination has 5,15% eficiency level.Key words: Solar Cell, Solar Simulator, Solar Cell Performance, solar Cell efficiency